Aflatoxin content and health risks associated with consumption of some herbal products sold in Kampala, Uganda - Onen, Patrick; Watmon, James; Omara, Timothy; Ocira, Daniel (Київський національний університет імені Тараса Шевченка, 2021)
Persuasive adverts and exaggeration of health benefits from consumption of herbal products as well as the mental picture of ‘natural’ is ‘safe’ has boosted traditional medicine use in Uganda. However, herbal products may be unsafe due to the possibility of their contamination with mycotoxins. In this study, we quantified the levels of aflatoxins (B1, B2, G1 and G2) in Real Koff product, Eddagala ly’e kifuba n’e senyiga, Omusujja, Cough mixture and Fever herbal products sold in Kampala, Uganda using high performance liquid chromatography-tandem mass spectrometry. The associated consumption health risks were assessed using the hazard index method. Only aflatoxin B1 was detected in 60% of the samples, with 40% of these surpassing WHO guidelines of ≤ 5 µg/kg. The hazard indices were all less than 1, implying that Ugandans who heavily rely on the herbal products are exposed to aflatoxins at sublethal doses which may lead to chronic effects in the long run. Studies using a larger sample size should assess whether the current observation is a routine occurrence or a sporadic event.
Keywords: aflatoxins; aflatoxicosis; estimated daily intake; hepatobiliary carcinoma; hazard index